Improving Artistic Creativity Through Fostering Karawitan Art For Youth Gong Groups In Ulian Village | Meningkatkan Kreativitas Seni Melalui Pembinaan Seni Karawitan Terhadap Sekaa Gong Remaja Di Desa Ulian - Aghastya Radha (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
Ulian Village, Kintamani District, Bangli Regency is one of the villages that is lagging behind in the field of musical arts. This backwardness is due to the absence of artistic figures who have become pioneers in both musical and other arts. The participation of Ulian Village in various performances held throughout the Kintamani District was also very minimal, Ulian Village had only participated in the event once. So from this the author chose Ulian Village as a Thematic Real Work Lecture (KKNT) partner. In Ulian Village, there are no artists who know about the Semarpegulingan gamelan, that the Semarpegulingan gamelan actually has a patet system and this gamelan is not like gong kebyar, so it sounds strange to the public's ears. The results of observations that the author observed in Ulian Village from an artistic perspective, namely karawitan art, mostly in this Ulian Village the percussion or gending that is played is percussion telu lembang, and there is gamelan semarpegulungan which is rarely used or played. The solution that we offer in this Thematic Real Work Lecture (KKNT), namely, training on gamelan semarpegulungan for youth sekha gong which will be initiated by the author. in this case students can contribute in providing reinforcement, training, and knowledge.